The Gender Wage Gap and Discrimination, East Germany 1990-1997 - Ira N. Gang; Myeong-Su Yun (Vierteljahrshefte zur Wirtschaftsforschung, 2001)
East Germany has undergone rapid transition from a socialist to a market economy since the fall of the Berlin Wall. We are interested in whether women are better off or worse off relative to men as a result of this transition. We use the German Socio-Economic Panel Data 1990-1997 to study wage determination and we implement a decomposition analysis that accounts for selection bias issues. Our analysis shows that even though the gender wage gap is shrinking, gender discrimination is not.
Keywords: 330; Übergangswirtschaft; Lohnstruktur; Fraueneinkommen; Neue Bundesländer; Geschlechterdiskriminierung; Tobit-Modell